The impact of marathon running on atrial remodeling in male and female amateur athletes assessed by three-dimensional echocardiography. (14th October 2021) - Lasocka, Z.B; Dabrowska-Kugacka, A; Kaleta-Duss, A; Lewicka-Potocka, Z; Faran, A; Danilowicz-Szymanowicz, L; Nowak, R; Kaufmann, D; Raczak, G; Lewicka, E
Abstract: Introduction: Endurance athletes have an increased risk of atrial remodeling and atrial arrhythmias. However, data regarding atrial adaptation to physical exercise in non-elite athletes are limited. We aimed to assess exercise-induced alternations in atrial morphology and function in male and female amateur marathon runners, using real-time three-dimensional (3D) echocardiography. Methods: The study group consisted of 40 male (39±8 years) and 27 female (40±7 years) amateur athletes. 3D echocardiography was performed 2–3 weeks before (Stage 1) and immediately after (Stage 2) the marathon run. Right (RA) and left atrial (LA) remodeling was assessed by volumetric measures, total ejection fraction (EF) and volume (EV). Speckle tracking was used to determine the temporal evaluation of atrial function by strain analysis. Results: The main results are presented in Table 1. At rest, male athletes demonstrated greater RA size and decreased RA contractility, as assessed by EF and atrial strains, in comparison to females. At Stage 1, LA morphology and function did not differ significantly between genders. After the marathon, a remarkable increase in RA maximal volume (RAVmax, 32.9±8.6 vs. 36.4±8.2 ml/m 2, p=0.016) and RAEF (49.5±9.7 vs. 57.3±9.2%, p=0.002) was observed only in female athletes (p<0.05 for both interactions sex and stage). Whereas in male runners, LA measures, such as LAVmax (30.7±6.4 vs. 26.8±6.2 ml/m 2, p=0.007), LAEF (56.7±4.3 vs. 52.7±5.3%, p=0.037) and LA conduit strain (LAScd, −18.7±8 vs. −13.6±8%, p=0.045), significantly decreased postrace. This observation was absent in females (p<0.05 for all interactions sex and stage). Conclusions: In amateur athletes, marathon running promotes biatrial remodelling with significant gender discrepancies. Females are more susceptible to exercise-induced morphological and functional changes of RA, while postrace alternations in males concern principally LA. 3D echocardiography of the atria is a useful indicator of exercise capacity, not only in elite, but also in amateur athletes. Funding Acknowledgement: Type of funding sources: None.